P686 Neither high infliximab maintenance doses nor high trough levels trigger skin side effects of the drug: a prospective cross-sectional study. (25th January 2019) - Kurent, T; Koren, U; Hanzel, J; Kozelj, M; Novak, G; Smrekar, N; Stabuc, B; Kecelj, N; Drobne, D
Abstract: Background: Skin lesions induced by infliximab are an important side effect and lead to drug discontinuation in many cases. It is not known whether these lesions occur more often with high-dose treatment or high drug concentrations that are needed to induce and maintain remission of IBD in some patients. We thus investigated whether high-dose infliximab treatment or high trough levels increase the incidence of skin lesions. Methods: This was a prospective observational cross-sectional study of all patients with IBD on infliximab maintenance treatment at a tertiary referral centre. Every patient's skin was examined by an experienced gastroenterologist and those with skin lesions were referred to a dermatologist for further evaluation. Furthermore, infliximab trough levels were measured and the dose of infliximab recorded in all patients. High-dose infliximab was defined as a maintenance dose of ≥10 mg/kg q 8 weeks and high trough levels as ≥7 µg/ml. Results: In total, we included 171 patients (103 CD, 63 UC, 5 IBD-unclassified). Skin lesions were observed in 40/171 (23%) patients (8 psoriatic, 7 psoriasiform eczema, 11 eczema, 4 xerosis, 10 others). Among patients on high-dose infliximab the incidence of skin lesions was not higher than in those with lower dose (9/53 [17%] vs. 31/118 [26%], p = 0.184). Similar was observed for patients with high vs. low trough levels (22/102 [22%] vs. 18/69 [26%], p = 0.493). Moreover, the median dose of administered infliximab was not different in patients with skin lesions compared with those without them (7.45 mg/kg q 8 weeks [IQR (interquartile range): 5.71–9.91] vs. 7.85 mg/kg q 8 weeks [IQR: 5.88-10.98], p = 0.741); the same was observed for median trough levels (7.46 µg/ml [IQR: 4.44–9.69] vs. 8.60 µg/ml [IQR: 5.48-12.00], p = 0.389). Finally, no differences were observed for specific skin lesions (Figures 1&2). Conclusions: In this prospective study, high-dose infliximab treatment or high infliximab trough levels were not associated with the occurrence of drug-induced skin lesions. This is a clinically important observation that enables the use of high-dose infliximab maintenance and targeting high trough levels when needed.